Honeycomb-like hierarchically porous carbon derived from waste biomass cork for efficient tetracycline removal - Jizhao ZHANG; Qihang WANG; Chengyu LI; Danwei HE; Jun MU (Meitan xuebao)
Hierarchical porous activated carbon (KHBC) with honeycomb structure was obtained by one-step slow pyrolysis using industrial waste cork particles as raw materials and KHC2O4 as activator, and it was applied to adsorb tetracycline hydrochloride (TC) in water. The relationship between activated carbon pore structure and adsorption performance was analyzed by fitting pore structure parameters with tetracycline adsorption capacity. Static adsorption experiments were conducted to investigate the effects of initial pH, temperature, initial concentration, and ionic strength on adsorption performance. The physicochemical structures of KHBC before and after adsorption were characterized using SEM and FT-IR techniques, establishing the correlation between the activation process, cork activated carbon pore structure, and adsorption performance. The results show that increasing the activation temperature and KHC2O4 addition ratio positively affects the specific surface area and total pore volume, promoting the formation of 2−5 nm mesopores. The specific surface area and total pore volume exhibit a strong linear relationship with TC adsorption capacity, with R2 values of 0.9852 and 0.958, respectively, and R2 of 0.8388 between 2−5 nm mesopore volume and TC adsorption capacity. At an activation temperature of 900 ℃ and an addition ratio of 5∶1, the resulting KHBC5-900 exhibits a specific surface area of 2447 m2/g, with a significant increase in 2−5 nm mesopores, showing the best adsorption effect on TC in water. It presents a micropore-mesopore pore size structure, with adsorption capacities of 1113.45 mg/g at 45 ℃ and 961.54 mg/g at 25 ℃, reaching 85% of the total adsorption in 5 minutes and equilibrium in 1 hour, which is 46 times that of un-activated BC-900 (21.25 mg/g). Also, the adsorption capacity is almost unaffected by environmental pH and ionic strength. The adsorption of TC by KHBC5-900 fits the quasi-second-order kinetic equation and Langmuir isotherm adsorption model, and the adsorption process is spontaneous and endothermic. The adsorption mechanism indicates that pore filling is the main adsorption mechanism, with the coexistence of π-π interactions and hydrogen bond interactions.